IMPLEMENTASI HASIL PENELITIAN IDENTIFIKASI FUNGI DALAM TAPE TALAS (COLOCASIA ESCULENTA) SEBAGAI SUMBER BELAJAR BERUPA MODUL PADA POKOK BAHASAN FUNGI TERHADAP KETERAMPILAN MENGINTERPRETASI DATA SISWA KELAS X SMA AL ISLAM 1 SURAKARTA TAHUN AJARAN 2011/2012 - Wulandari, Badrisyiyani Eko; Harlita, Harlita; Muzayyinah, Muzayyinah (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT - This is an experimental research of which result is implemented in the learning process of Biology subject in the Xth grade of senior high school. The objectives of this research are: (1) to find out kinds of fungal in taro tape (Colocasia esculenta) according to their morphological characteristics, (2) to find out the effect of the utilization of the research result of identification as a modul-based learning source towards the interpreting data skill of the Xth grade of SMA Al Islam 1 Surakarta Academic Year 2011/2012. The implementation of the research result towards biology learning process in the Xth grade of senior high school was a quasi-experimental research. The independent variable in this research is the modul-based learning source whereas the dependent variable is the interpreting data skill. The population of the fungal identification in taro tape (colocasia esculenta) was all the fungal in taro tape. The population of the implementation of the research result towards the learning process of fungal chapter was all of the students of the Xth grade of SMA Al Islam 1 Surakarta Academic Year 2011/2012. The sample of the implementation of the research result towards the learning process of fungal chapter of Biology subject consisted of two classes, i.e. control and experiment class. The sampling method used cluster random sampling. The data collecting technique of fungal identification research was experimentation and documentation whereas the implementation of the research result towards the interpreting data skill used observation methods. The test of the hypothesis for the implementation of the research result towards the learning process of biology used t-test. From the research, it can be concluded that (1) there are two kind genus of fungal in taro tape, i.e. genus Saccharomyces dan genus Aspergillus which identified according to their morphological characteristics, (2) the utilization of the research result of fungal identification in taro tape (colocasia esculenta) a modul-based learning source has a tangible impact towards the interpreting data skill of the xth grade of SMA Al Islam 1 Surakarta Academic Year 2011/2012. Keywords: fungal identification, learning source, interpreting data skill